Interpreting Hadith on Marriage Preferences Through Gadamer's Hermeneutics: Integrating Classical Textual Meaning With Modern Social Relevance - PK, Moh. Nurun Alan Nurin; Qudsia, Miatul; Irfani, Muhammad Syahru (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
The hadith on preferences in choosing a life partner “Women are married for four reasons…” is frequently interpreted in a partial and hierarchical manner, placing physical aspects such as beauty, wealth, and lineage on the same level as, or even above, religious values. Such textual-literal readings reproduce patriarchal norms and overlook the historical context of the hadith’s emergence. This study reinterprets the hadith through Hans-Georg Gadamer’s philosophical hermeneutics, emphasizing pre-understanding and the fusion of horizons between text and reader. Using a qualitative–critical approach and drawing on both classical (turāth) and contemporary scholarship, this research finds that religion in the hadith is not merely one of four equal considerations but serves as a normative critique of the materialistic and status-oriented tendencies of Arab society at the time. Non-physical criteria such as moral integrity, responsibility, and mutual respect represent the core religious values that should be prioritized. Through Gadamerian hermeneutics, the hadith is contextualized as an ethical guideline for forming marital relationships that are balanced, just, and free from patriarchal domination, reaffirming the primacy of religious values in contemporary practice